Relationship between FAT/CD36 protein in skeletal muscle and whole-body fat oxidation in endurance-trained mice - Kim, Jisu (J Exerc Nutrition Biochem, 2016)
[PURPOSE]: We investigated the effects of endurance training on the expression of long-chain fatty acid transport proteins in the skeletal muscle and whole-body fat oxidation during endurance exercise. [METHODS]: Seven-week-old male ICR mice (n = 12) were divided into 2 groups, namely, Sed (sedentary; non-trained) and Tr (endurance-trained) groups. The Tr group was adapted to treadmill training at a fixed intensity (15 m/min, 8° slope) for 3 days. Next, the exercise intensity was increased while maintaining the 8° slope. In the last week of training, the exercise intensity was set at 25 m/min for 50 min (about 70–75% maximal oxygen uptake for 4 weeks). After the protocol ended, the mice were sacrificed, and tissues were collected for western blot analysis. [RESULTS]: Four weeks of endurance training resulted in a significant increase in the protein levels of FAT/CD36 and CPTІ. The FAT/ CD36 protein level in the Tr group was about 1.3-fold greater than that in the Sed group (p < 0.01). Furthermore, the increased CPTІ indicated higher activity (19% upregulation) in the Tr group compared to the Sed group (p < 0.05). The FAT/CD36 protein level and the estimated whole-body fat oxidation rate during 1-h exercise were found to be significantly correlated (r = 0.765, p < 0.01). [CONCLUSION]: We suggest that the increase in FAT/CD36 protein in skeletal muscle by endurance training might be positively associated with whole-body fat oxidation, which might enhance endurance exercise capacity.